Calculation of mathematical models of biological type multiplication and growth - Antanas Lapinskas; Renatas Lapinskas (Lietuvos Matematikos Rinkinys)
Simulating scheme of calculation of mathematical models of biological object multiplication and growth has been performed with usage of simulating modelling system. Calculation scheme consist of 3 subsystems: simulation of design parameters, simulation of external effects and calculation of state parameters. Calculation scheme are suitable for designing virtual biological systems. General design principles of such systems have been discussed.